Financial Literacy and the Financial Crisis - Klapper, Leora; Lusardi, Annamaria; Panos, Georgios A. (2012)
The ability of consumers to make informed financial decisions improves their chances of having sound personal finance. This paper uses a panel dataset from Russia, where consumer loans grew at an astounding rate -- from about US$10 billion in 2003 to over US$170 billion in 2008 -- to examine the importance of financial literacy and its relationship with behavior. The survey asked questions on financial literacy, consumer borrowing (formal and informal), and spending behavior. The paper studies the consequences of greater financial literacy on the use of financial products and financial planning. Even though consumer borrowing rose rapidly in Russia, only 41 percent of the survey respondents understood how interest compounding worked and only 46 percent could answer a simple question about inflation. Financial literacy is positively related to participation in financial markets and negatively related to the use of informal sources of borrowing. Individuals with higher rates of financial literacy are significantly more likely to report having more unspent income at the end of the month and higher spending capacity. The relationship between financial literacy and the availability of unspent income is more evident during the financial crisis, suggesting that better financial literacy may better equip individuals to deal with macroeconomic shocks.